Corporate governance, firm size, and tax avoidance: How does corporate governance influence tax avoidance across small and large Philippine firms? - Ang, Christine E. (Animo Repository, 2023)
Corporate taxes represent costs that are proportional to an entity’s profit, which could substantially impact a firm’s financial bottom line. To improve profitability, many firms have turned to engaging in tax avoidance activities. However, there is growing evidence from recent literature that investors generally value tax avoidance negatively (Assidi et al., 2016; Chen et al., 2014; Herron & Nahata, 2020). Likewise, tax avoidance harms the state by depriving it of tax revenues. If tax avoidance is value-destroying then, good corporate governance mechanisms intended to maximize stakeholder value should limit tax avoidance behavior (Kerr et al., 2016; Aburajab et al., 2019). We extend this analysis further by investigating the potential moderating role of firm size on the effect of corporate governance on tax avoidance. The oversight effect of corporate governance on tax avoidance should be stronger in larger firms, as they are subject to greater reputational risks, following the legitimacy theory (Jensen & Meckling, 1976; Watts & Zimmerman, 1986; Sopiyana, 2022). We employed a two- step generalized method of moments estimation technique to test these hypotheses. Consistent with both the agency and legitimacy theory, we found that corporate governance has a significant negative effect on corporate tax avoidance. We then found that firm size also has a significant negative effect on corporate tax avoidance, following the political cost theory. Finally, we found that firm size positively moderates the effect of corporate governance on tax avoidance. Drawing on these empirical results, we make several recommendations to our primary stakeholders.